Occult Liver Abscess Following Clinically Unsuspected Ingestion of Foreign Bodies - Ban CH Tsui; J Mossey (Canadian Journal of Gastroenterology)
Two uncommon cases of foreign body (a wooden clothespin and a toothpick) perforation of the gut with associated pyogenic liver abscesses are presented. These cases illustrate the difficulties of preoperative diagnosis. The lack of history of ingestion of foreign bodies, variable clinical presentation of the conditions and radiolucent natures of the foreign bodies all play a role in impeding the diagnosis preoperatively. This report emphasizes the role of ultrasound and computed tomographic scan in evaluating similar cases. Any patient with known risk factors for ingestion of foreign body should arouse suspicion and be investigated further.